Heat affected zone in the laser-assisted milling of Inconel 718. (December 2017) - Pan, Zhipeng; Feng, Yixuan; Hung, Tsung-Pin; Jiang, Yun-Chen; Hsu, Fu-Chuan; Wu, Lung-Tien; Lin, Chiu-Feng; Lu, Ying-Cheng; Liang, Steven Y.
Abstract: The melting zone shape is experimentally characterized in the laser-assisted milling process of Inconel 718. A three-dimensional finite element model is proposed for the temperature field distribution prediction. A good agreement is found between the experimental characterized melting zone shape and predicted melting zone shape. The material absorption ratio is determined by matching the melting zone shape from experiment with simulation model. The material absorption ratio is found to be a weak function of laser scanning speed. With the increase of laser power input, the absorption ratio monotonically decreases. The effects of laser scanning speed and power input on the melting zone shape are investigated. The melting zone depth, width and cross section area decrease with the increasing of laser scanning speed and increase with increasing power input.